2012
DOI: 10.1177/0363546512467621
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Fibrin Matrix in the Management of Arthroscopic Repair of the Rotator Cuff

Abstract: Platelet-rich fibrin matrix was not shown to significantly improve perioperative morbidity, clinical outcomes, or structural integrity. While longer term follow-up or different platelet-rich plasma formulations may show differences, early follow-up does not show significant improvement in perioperative morbidity, structural integrity, or clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
129
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(139 citation statements)
references
References 34 publications
5
129
0
5
Order By: Relevance
“…Lee et al [62] RCT [75] RCT 60 pts/12 mo MRI Healing rates did not differ between groups Ⅰ augmentation group (20%) significantly lower than in the non-augmented group (56%) (P = 0.023).…”
Section: Rehabilitationmentioning
confidence: 92%
See 1 more Smart Citation
“…Lee et al [62] RCT [75] RCT 60 pts/12 mo MRI Healing rates did not differ between groups Ⅰ augmentation group (20%) significantly lower than in the non-augmented group (56%) (P = 0.023).…”
Section: Rehabilitationmentioning
confidence: 92%
“…There is currently no consensus on PRP application during rotator cuff repair as several studies have shown a positive effect on healing while others have shown no effect or a negative effect. Weber et al [75] performed a prospective randomized study evaluating the effects of platelet rich fibrin matrix (PRFM) on tendon healing and found no differences in healing rates in PRFM treated repairs compared to controls. Rodeo et al [76] reported similar results for PRFM in a randomized control trial where healing rates in the PRFM group were 67% compared to 81% in the non-augmented repairs (P = 0.2).…”
Section: Platelet Rich Plasmamentioning
confidence: 99%
“…25,29 Risk of Bias Assessment Figure 2 summarizes the results of the risk of bias evaluation for each study. The risk of bias was found to be high for 5 of 11 studies (45.5%) regarding randomization procedures (selection bias) [26][27][28]41,43 and for 7 of 11 (63.6%) studies regarding performance bias. 21,25,[27][28][29]31 In 6 of 11 studies (54.5%), the completeness of the 26 9 mL blood drawn, mixed with anticoagulant and separator gel, centrifuged for 6 min at 1,100 rpm Supernatant mixed with calcium chloride in Wheaton bottle, centrifuged again at 4,500 RCF for 25 min PRFM formed at bottom of container PRFM inserted between tendon and footprint Double-row repair using 1 metal anchor medially (mattress configuration with nonsliding knot) and 2 anchors laterally tied using sliding knot with 3 alternating half-hitches Shoulders immobilized in abduction for 3 wk Pendulum exercises allowed immediately postoperatively Passive ROM and active-assisted ROM for FF and ER at 3 wk Rotator cuff and periscapular strengthening at 6 wk Return to light activity at 3 mo, full activity at 6 mo Randelli et al 21 54 mL of blood drawn, mixed with 6 mL anticoagulant and centrifuged for 15 min at 3,200 rpm PRP isolated from floating buoy PRP mixed with concentrated fibrinogen and thrombin that was obtained using other procedures PRP injected into dry subacromial space between the repaired tendon and footprint…”
Section: Study Selectionmentioning
confidence: 97%
“…Three of these studies were excluded, leaving a total of 9 included studies. 21,[25][26][27][28][29][41][42][43] Manual text and reference list searches revealed 2 additional studies that were also included. 30,31 Therefore, a total of 11 studies were included in this review, and a maximum of 8 studies were used for each meta-analysis according to data availability.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation